2017
DOI: 10.5433/1679-0359.2017v38n3p1169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variable-row-spacing harvesting picker platform scraping plates on cotton fiber quality and quantity

Abstract: There have been increasing demands for high-quality cotton fibers that meet the textile industry quality standards. Concurrently, there have been efforts to reduce contaminants during harvesting to reduce harvesting costs. The goal of this research was to evaluate the efficiency of the picker platform with Variable-Row-Spacing (VRS) for harvesting cotton in narrow rows, over two harvest seasons in two regions within the state of Mato Grosso, Brazil. In this study, how the presence vs. absence of scraping plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In this study, how the effect of scraping plates and travel speed was related to quantifiable levels of harvested fibers and impurities for various cotton varities with row spacing of 0.45 m. The results revealed that scraping plates reduced the harvest efficiency and increased the number of stems and cones for cotton planted in narrow rows. The highest speed and the presence of the scraping plates increased the number of cones and the removal of the scraping plates decreased the amount of cones in the harvested cotton (Baraviera et al, 2017).…”
Section: Weather and Other Factorsmentioning
confidence: 95%
“…In this study, how the effect of scraping plates and travel speed was related to quantifiable levels of harvested fibers and impurities for various cotton varities with row spacing of 0.45 m. The results revealed that scraping plates reduced the harvest efficiency and increased the number of stems and cones for cotton planted in narrow rows. The highest speed and the presence of the scraping plates increased the number of cones and the removal of the scraping plates decreased the amount of cones in the harvested cotton (Baraviera et al, 2017).…”
Section: Weather and Other Factorsmentioning
confidence: 95%